A kind of iron-making blast furnace branch ditch castable and preparation method thereof

By adopting specific formulas and processes in blast furnace branch groove castables, the problems of short service life and insufficient performance in complex working conditions are solved, and higher refractory resistance, oxidation resistance and service life are achieved.

CN117510190BActive Publication Date: 2025-03-25SHANGHAI LIER REFRACTORY MATERIAL +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311502379.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2025-03-25
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

The castable material in the existing blast furnace discharge groove lining is high in energy consumption, strength, erosion resistance, low corrosion resistance and short service life under complex working conditions.

Method used

A kind of iron-smelting blast furnace branch groove castable is used, and its raw material formula includes alumina, plate-shaped corundum, silicon carbide, alumina micro powder, boron nitride-silicon carbide composite powder and rosystone. Through specific ratios and processes, the bonding, refraction and oxidation resistance of the castable are improved.

Benefits of technology

It significantly improves the service life and performance of blast furnace branch groove castable, enhances its oxidation, erosion and erosion resistance, and reduces production costs and maintenance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a branch ditch castable for an ironmaking blast furnace and a preparation method thereof, and relates to the technical field of refractory materials. The mass percentage of each raw material in the castable is: 11-12% of 15-8mm bauxite, 13-14% of 8-5mm bauxite, 11-13% of 5-3mm bauxite, 11-12% of 3-1mm bauxite, 8-9% of 3-1mm plate-shaped corundum, 4-5% of 1-0mm plate-shaped corundum, 10-12% of 1-0mm silicon carbide, 9-10% of 325 mesh silicon carbide, and 10% of 2 ... Alumina powder 4.5-5.5%, silica powder 1.5-2.5%, high alumina cement 1.5-2%, ρ-Al2O3 0.5-1%, andalusite 1-1.5%, spherical asphalt 2-2.5%, graphite powder 1.5-2%, boron carbide 0.2-0.4%, boron nitride-silicon carbide composite powder 0.3-0.5%, metallic silicon powder 1.5-2%, metallic aluminum powder 0.02-0.04%, organic fiber 0.04-0.07%, water reducer 0.1-0.3%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a branch ditch castable for an ironmaking blast furnace and a preparation method thereof. Background Art

[0002] Ironmaking is the process of converting iron oxide into elemental iron and slag by reducing the iron-containing substances in various iron ores (mainly magnetite and hematite) in nature. The current mature process methods include blast furnace reduction ironmaking, molten reduction ironmaking and direct reduction ironmaking. Among them, the blast furnace reduction ironmaking process has the advantages of maturity and stability, large output, high thermal efficiency, low energy consumption and low operating costs, and is currently the dominant process for ironmaking. my country is the world's largest country in steel production, showing a situation where super-large and large blast furnaces coexist with small and medium-sized blast furnaces. There are also various types of blast furnace tapping channels, and the amount of steel produced during the service life is also uneven, which is not conducive to the scientific, stable and sustainable development of the steel industry.

[0003] The high-temperature liquid iron and slag reduced by the blast furnace flow into the downstream production process through the main ditch and branch ditch channels of the blast furnace iron-making yard. Therefore, the blast furnace iron ditch channel is the key guarantee for the stable production and continuous operation of the blast furnace. Al2O3-SiC-C system castables are widely used in the lining casting refractory materials of the blast furnace iron-making ditch. During use, they are affected by various complex environments and their service life is damaged in multiple ways, especially the occurrence of oxidation reactions, which leads to the reduction of their strength and anti-scouring and anti-erosion capabilities.

[0004] Therefore, under the complex working conditions of rapid cooling and heating, improving the performance of Al2O3-SiC-C system castables and extending their service life have certain practical significance for ensuring the stable operation of blast furnaces and helping the steel industry to save energy and reduce emissions. Summary of the invention

[0005] Aiming at the defects and problems of existing blast furnace tapping ditch lining casting refractory materials, such as high energy consumption, low strength and anti-scouring and anti-erosion capabilities, and short service life, the present invention provides an ironmaking blast furnace branch ditch castable and a preparation method thereof.

[0006] The solution adopted by the present invention to solve the technical problem is: a castable for a branch ditch of an ironmaking blast furnace, wherein the mass percentage of each raw material component in the castable is: 11-12% of 15-8mm alumina, 13-14% of 8-5mm alumina, 11-13% of 5-3mm alumina, 11-12% of 3-1mm alumina, 8-9% of 3-1mm plate-shaped corundum, 4-5% of 1-0mm plate-shaped corundum, 10-12% of 1-0mm silicon carbide, 9-10% of 325 mesh silicon carbide, and 10% of 20% oxygen. The content of alumina powder is 4.5-5.5%, silica powder is 1.5-2.5%, high alumina cement is 1.5-2%, ρ-Al2O3 is 0.5-1%, andalusite is 1-1.5%, spherical asphalt is 2-2.5%, graphite powder is 1.5-2%, boron carbide is 0.2-0.4%, boron nitride-silicon carbide composite powder is 0.3-0.5%, metallic silicon powder is 1.5-2%, metallic aluminum powder is 0.02-0.04%, organic fiber is 0.04-0.07%, and water reducer is 0.1-0.3%.

[0007] Furthermore, the mass percentage of each raw material component in the blast furnace branch ditch castable is: 15-8mm bauxite is 11.5%, 8-5mm bauxite is 13.5%, 5-3mm bauxite is 12.5%, 3-1mm bauxite is 11.5%, 3-1mm plate corundum is 8.5%, 1-0mm plate corundum is 4.5%, 1-0mm silicon carbide is 11%, 325 mesh silicon carbide is 9.5%, alumina powder is 5%, silicon powder is 2%, high alumina cement is 1.8%, ρ-Al2O3 is 0.7%, andalusite is 1.3%, spherical asphalt is 2.25%, graphite powder is 1.8%, boron carbide is 0.3%, boron nitride-silicon carbide composite powder is 0.4%, metallic silicon powder is 1.7%, metallic aluminum powder is 0.02%, organic fiber is 0.05%, and water reducer is 0.18%.

[0008] Furthermore, in each component of the castable, Al2O3≥87% and Fe2O3≤1.5% in alumina; Al2O3≥99% and Fe2O3≤0.1% and SiO2≤0.1% in plate-shaped corundum; SiC≥97% and SiO2≤0.4% and Fe2O3≤0.3% and free carbon≤0.5% in silicon carbide; the particle size of alumina micropowder is ≤1µm; SiO2≥95% in silicon micropowder; Al2O3≥80% in high alumina cement; Al2O3≥92% in ρ-Al2O3; Al2O3≥57% and the particle size is 325 mesh in spherical The fixed carbon content in asphalt is ≥60%, the ash content is ≤0.2%, the volatile matter is ≤40%, the particle size of 1-0.5mm accounts for 65%, and the particle size of 0.5-0.1mm accounts for 35%; the fixed carbon content in graphite powder is ≥94%, the ash content is ≤1.6%, and the volatile matter is ≤1%; the B4C in boron carbide is ≥95%, SiO2 is ≤0.1%, and Fe2O3 is ≤0.25%; the particle size of boron nitride-silicon carbide composite powder is 800 mesh, of which boron nitride accounts for 22% and silicon carbide accounts for 78%; the particle size of metal silicon powder is 325 mesh; the particle size of metal aluminum powder is 200 mesh; the water reducer is a polyethylene glycol-based water reducer.

[0009] Furthermore, the surface of the graphite powder is modified by impregnation with trimethylaluminum, and the proportion of the sites modified by trimethylaluminum to the total carbon edge sites is ≥60%.

[0010] Furthermore, the iron ditch castable is used for branch ditch of blast furnace iron ditch.

[0011] The present invention also provides a method for preparing a branch ditch castable for an ironmaking blast furnace, comprising the following steps:

[0012] S1. According to the weight percentage, weigh 325 mesh silicon carbide, alumina powder, silicon powder, high alumina cement, ρ-Al2O3, andalusite, spherical asphalt, graphite powder, boron carbide, boron nitride-silicon carbide composite powder, metal silicon powder, metal aluminum powder, organic fiber, and water reducer respectively, add them into a mixer and stir for 5 to 7 minutes to obtain a small batch for standby use;

[0013] S2, weighing 15-8mm alumina, 8-5mm alumina, 5-3mm alumina, 3-1mm alumina, 3-1mm plate-shaped corundum, 1-0mm plate-shaped corundum, and 1-0mm silicon carbide according to weight percentage, adding them into a mixer in sequence and stirring for 3 to 5 minutes to obtain compound granules;

[0014] S3. While stirring the compound granular material, continuously and evenly add the compound small material to the mixer. The adding time of the compound small material is 3 to 5 minutes. After the addition is completed, the mixture of the compound granular material and the compound small material is evenly stirred for 3 to 5 minutes. After packaging, the blast furnace branch ditch castable can be obtained.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The invention provides an ironmaking blast furnace branch ditch castable and a preparation method thereof, wherein spherical asphalt with a particle size of 1-0.5 mm accounts for 65% and with a particle size of 0.5-0.1 mm accounts for 35%, and the bonding performance and refractory performance of the iron hook castable can be improved; boron nitride-silicon carbide composite powder is also added to the raw materials to improve the oxidation resistance of the iron ditch castable, thereby improving the service life of the iron ditch; andalusite is also added, the purpose of which is to generate a liquid phase containing SiO2 under high temperature conditions during the production process of the blast furnace branch ditch castable, penetrate into tiny pores under the capillary force in the castable, block the channel, and prevent the reaction between oxygen and the material inside the castable, and the liquid phase rich in SiO2 is easy to react with Al2O3 in the castable to generate mullite, so as to make the castable structure more compact and hinder the penetration of oxygen into the castable, thereby improving the oxidation resistance of the castable.

[0017] The raw material formula of the ironmaking blast furnace branch ditch castable of the present invention has the advantages of good refractory performance, strong wear resistance, good uniformity, strong slag resistance, low production cost, good environmental protection, etc.; the preparation method is beneficial to improving the performance and quality stability of the blast furnace branch ditch castable, while improving production efficiency, reducing production costs, and reducing the maintenance cost and construction work intensity of the blast furnace branch ditch.

[0018] Moreover, after performance testing, the bulk density, flexural strength and compressive strength test results of the branch ditch castable of the present invention are all within the range of qualified product inspection indicators. The excellent refractory properties as well as high hardness and high strength are maintained, so that the castable prepared by the present invention has good antioxidant properties, which significantly improves the performance and service life of the blast furnace branch ditch castable. Implementation

[0019] The present invention is further described below in conjunction with embodiments. Example

[0020] The present embodiment provides a blast furnace branch ditch castable for ironmaking, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 11.5% of 15-8mm alumina, 13.5% of 8-5mm alumina, 12.5% ​​of 5-3mm alumina, 11.5% of 3-1mm alumina, 8.5% of 3-1mm plate-shaped corundum, 4.5% of 1-0mm plate-shaped corundum, and 11% of 1-0mm silicon carbide. The content of 325 mesh silicon carbide is 9.5%, alumina powder is 5%, silicon powder is 2%, high alumina cement is 1.8%, ρ-Al2O3 is 0.7%, andalusite is 1.3%, spherical asphalt is 2.25%, graphite powder is 1.8%, boron carbide is 0.3%, boron nitride-silicon carbide composite powder is 0.4%, metallic silicon powder is 1.7%, metallic aluminum powder is 0.02%, organic fiber is 0.05%, and water reducer is 0.18%.

[0021] Among the above components, Al2O3 in bauxite is ≥87%, Fe2O3 is ≤1.5%; Al2O3 in plate-shaped corundum is ≥99%, Fe2O3 is ≤0.1%, SiO2 is ≤0.1%; SiC in silicon carbide is ≥97%, SiO2 is ≤0.4%, Fe2O3 is ≤0.3%, and free carbon is ≤0.5%; the particle size of alumina powder is ≤1µm; SiO2 in silica powder is ≥95%; Al2O3 in high alumina cement is ≥80%; Al2O3 in ρ-Al2O3 is ≥92%; Al2O3 in andalusite is ≥57%, and the particle size is 325 mesh; Fixed carbon ≥ 60%, ash ≤ 0.2%, volatile matter ≤ 40%, particle size of 1-0.5mm accounts for 65%, and particle size of 0.5-0.1mm accounts for 35%; fixed carbon in graphite powder ≥ 94%, ash ≤ 1.6%, volatile matter ≤ 1%; B4C in boron carbide ≥ 95%, SiO2 ≤ 0.1%, Fe2O3 ≤ 0.25%; the particle size of boron nitride-silicon carbide composite powder is 800 mesh, of which boron nitride accounts for 22% and silicon carbide accounts for 78%; the particle size of metal silicon powder is 325 mesh; the particle size of metal aluminum powder is 200 mesh; the water reducer is a polyethylene glycol-based water reducer.

[0022] Among the raw materials constituting the castable of the present invention, 65% of the spherical asphalt has a particle size of 1-0.5 mm, and 35% has a particle size of 0.5-0.1 mm. This is because the particle size of the spherical asphalt has a great influence on the performance and process of the iron hook castable. The smaller the particle size of the spherical asphalt, the larger the surface area, and the larger the contact area with other raw materials, which can improve the bonding performance and fire resistance of the iron hook castable. However, if the particle size of the spherical asphalt is too small, the flowability will deteriorate, affecting the casting construction. Therefore, the spherical asphalt selected by the present invention has the best comprehensive performance.

[0023] The raw materials constituting the blast furnace branch ditch castable of the present invention are added with boron nitride-silicon carbide composite powder to improve the anti-oxidation performance of the iron ditch castable, thereby improving the service life of the iron ditch. In the boron nitride-silicon carbide composite powder, boron nitride accounts for 22%, silicon carbide accounts for 78%, and the boron nitride and silicon carbide in the raw materials are both 400 mesh. During hot pressing, the temperature is 1850-1870°C and the pressure is 130-150Mpa. Under such conditions, the optimal performance of the boron nitride-silicon carbide composite powder is prepared, and excellent anti-oxidation performance is achieved on the basis of ensuring excellent physical and chemical indicators and appropriate raw material prices, thereby effectively extending the service life of the iron ditch.

[0024] Boron nitride-silicon carbide composite powder has the excellent antioxidant properties of boron nitride, which can form a stable oxide protective layer at high temperature to prevent further oxidation of the material, as well as the excellent properties of silicon carbide such as high hardness, high melting point and high strength, which can effectively resist the oxidation and reaction of the castable at high temperature. The combination of the two realizes the formation of a stable antioxidant protective film layer at high temperature and maintains high hardness and high strength, thereby significantly improving the antioxidant properties of the castable.

[0025] The present invention further adds andalusite into the raw material of the blast furnace branch ditch castable, with the purpose of generating a liquid phase containing SiO2 under high temperature conditions during the production process of the blast furnace branch ditch castable, and infiltrating into tiny pores under the capillary force in the castable to block the channel and prevent the reaction between oxygen and the material inside the castable, and the liquid phase rich in SiO2 is easy to react with Al2O3 in the castable to generate mullite, which makes the castable structure more compact and hinders the infiltration of oxygen into the castable, thereby improving the anti-oxidation performance of the castable.

[0026] Based on the above raw material ratio of blast furnace branch ditch castable, this embodiment also provides a method for preparing blast furnace branch ditch castable, and the process includes the following steps:

[0027] S1. According to the above mass percentages, weigh 325 mesh silicon carbide, alumina powder, silicon powder, high alumina cement, ρ-Al2O3, andalusite, spherical asphalt, graphite powder, boron carbide, boron nitride-silicon carbide composite powder, metallic silicon powder, metallic aluminum powder, organic fiber, and water reducer, add them into a mixer in sequence and stir for 6 minutes to obtain a small batch;

[0028] S2, according to the above weight percentage, weigh 15-8mm alumina, 8-5mm alumina, 5-3mm alumina, 3-1mm alumina, 3-1mm plate-shaped corundum, 1-0mm plate-shaped corundum, and 1-0mm silicon carbide, add them into a mixer in sequence and stir for 3 minutes to obtain compound granules;

[0029] S3. While uniformly stirring the stirrer filled with the compound granular material, continuously and uniformly add the compound small material into the mixer. The adding time of the compound small material is 3 minutes. After the addition is completed, stir for another 3 minutes. After packaging, the blast furnace branch ditch castable is obtained.

[0030] In order to further improve the anti-oxidation performance of graphite powder, trimethylaluminum is used to impregnate the surface of the graphite powder, and the treatment process is as follows:

[0031] ① Add graphite powder into the reactor, add appropriate amount of n-hexane, toluene, etc., and stir evenly;

[0032] ② Add 5% trimethylaluminum by weight of graphite powder into the reactor and continue stirring evenly;

[0033] ③ Heat the reactor, keep the temperature at 90-100°C, stir and react for 4-5 hours, so that trimethylaluminum reacts with the hydroxyl or carbonyl group on the surface of the graphite powder to form a chemical bond, and tightly bind the trimethylaluminum and graphite powder together;

[0034] ④ After the reaction is completed, wash with a solvent to remove unreacted trimethylaluminum and other impurities;

[0035] ⑤ Place the washed graphite powder in a ventilated drying room to dry it and remove the residual solvent to obtain trimethylaluminum-modified graphite powder; the ratio of the sites modified by trimethylaluminum to the total carbon edge sites is ≥60%, and the modified graphite powder has excellent antioxidant properties under high temperature conditions. Example

[0036] The present embodiment provides a blast furnace branch ditch castable and a preparation method thereof, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 11% of 15-8mm alumina, 13.8% of 8-5mm alumina, 11% of 5-3mm alumina, 11.8% of 3-1mm alumina, 8.9% of 3-1mm plate-shaped corundum, 4.4% of 1-0mm plate-shaped corundum, 12% of 1-0mm silicon carbide, 9.3% of 325 mesh silicon carbide, 4.8% of alumina micropowder, 2.4% of silicon micropowder, 2% of high alumina cement, 0.8% of ρ-Al2O3, 1% of garnet, 2.3% of spherical asphalt, 1.6% of graphite powder, 0.25% of boron carbide, 0.35% of boron nitride-silicon carbide composite powder, 2% of metallic silicon powder, 0.03% of metallic aluminum powder, 0.07% of organic fiber, and 0.2% of water reducer. Other conditions are the same as those in Example 1.

[0037] Based on the above raw material ratio of blast furnace branch ditch castable, this embodiment also provides a method for preparing blast furnace branch ditch castable, and the process includes the following steps:

[0038] S1. According to the above mass percentages, 325 mesh silicon carbide, alumina powder, silicon powder, high alumina cement, ρ-Al2O3, andalusite, spherical asphalt, graphite powder, boron carbide, boron nitride-silicon carbide composite powder, metallic silicon powder, metallic aluminum powder, organic fiber, and water reducer are weighed and added to a mixer in sequence for stirring for 7 minutes to obtain a small batch;

[0039] S2, according to the above weight percentage, weigh 15-8mm bauxite, 8-5mm bauxite, 5-3mm bauxite, 3-1mm bauxite, 3-1mm plate-shaped corundum, 1-0mm plate-shaped corundum, and 1-0mm silicon carbide, add them into a mixer in sequence and stir for 5 minutes to obtain compound granules;

[0040] S3. While uniformly stirring the stirrer filled with the compound granular material, continuously and uniformly add the compound small material into the mixer. The adding time of the compound small material is 3 minutes. After the addition is completed, stir for another 3 minutes. After packaging, the blast furnace branch ditch castable is obtained. Example

[0041] The present embodiment provides a blast furnace branch ditch castable and a preparation method thereof, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 11.7% of 15-8mm alumina, 14% of 8-5mm alumina, 12.8% of 5-3mm alumina, 11% of 3-1mm alumina, 8.7% of 3-1mm plate-shaped corundum, 4% of 1-0mm plate-shaped corundum, 10.5% of 1-0mm silicon carbide, 9% of 325 mesh silicon carbide, 5.3% of alumina micropowder, 2.5% of silicon micropowder, 1.6% of high alumina cement, 0.6% of ρ-Al2O3, 1.5% of andalusite, 2.33% of spherical asphalt, 2% of graphite powder, 0.2% of boron carbide, 0.4% of boron nitride-silicon carbide composite powder, 1.5% of metallic silicon powder, 0.02% of metallic aluminum powder, 0.05% of organic fiber, and 0.3% of water reducer. Other conditions are the same as those in Example 1, and the preparation method of the branch ditch castable for the ironmaking blast furnace in this embodiment is the same as that in Example 1. Example

[0042] The present embodiment provides a blast furnace branch ditch castable and a preparation method thereof, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 12% of 15-8mm alumina, 13.8% of 8-5mm alumina, 12.7% of 5-3mm alumina, 12% of 3-1mm alumina, 9% of 3-1mm plate-shaped corundum, 4.8% of 1-0mm plate-shaped corundum, 10% of 1-0mm silicon carbide, and 10% of 32-1mm alumina. 5 mesh silicon carbide is 9.8%, alumina powder is 4.5%, silicon powder is 1.5%, high alumina cement is 1.7%, ρ-Al2O3 is 0.5%, andalusite is 1.3%, spherical asphalt is 2.1%, graphite powder is 1.7%, boron carbide is 0.3%, boron nitride-silicon carbide composite powder is 0.5%, metal silicon powder is 1.6%, metal aluminum powder is 0.03%, organic fiber is 0.04%, and water reducer is 0.13%. Other conditions are the same, and the preparation method is as described in Example 1. Example

[0043] The present embodiment provides a blast furnace branch ditch castable and a preparation method thereof, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 11.4% of 15-8mm alumina, 13.6% of 8-5mm alumina, 11.8% of 5-3mm alumina, 11.3% of 3-1mm alumina, 8% of 3-1mm plate-shaped corundum, 4.9% of 1-0mm plate-shaped corundum, and 11.5% of 1-0mm silicon carbide. %, 325 mesh silicon carbide is 10%, alumina powder is 4.9%, silicon powder is 2.1%, high alumina cement is 1.5%, ρ-Al2O3 is 1%, andalusite is 1.2%, spherical asphalt is 2.5%, graphite powder is 1.5%, boron carbide is 0.2%, boron nitride-silicon carbide composite powder is 0.42%, metal silicon powder is 1.8%, metal aluminum powder is 0.04%, organic fiber is 0.06%, and water reducer is 0.28%. Other conditions are the same, and the preparation method is as described in Example 1. Example

[0044] The present embodiment provides a blast furnace branch ditch castable and a preparation method thereof, wherein the mass percentages of the raw materials constituting the blast furnace branch ditch castable are: 11.2% of 15-8mm alumina, 13% of 8-5mm alumina, 13% of 5-3mm alumina, 11.2% of 3-1mm alumina, 8.3% of 3-1mm plate-shaped corundum, 5% of 1-0mm plate-shaped corundum, and 10.4% of 1-0mm silicon carbide. , 325 mesh silicon carbide is 9.7%, alumina powder is 5.5%, silicon powder is 2.5%, high alumina cement is 1.7%, ρ-Al2O3 is 0.7%, andalusite is 1.4%, spherical asphalt is 2%, graphite powder is 1.8%, boron carbide is 0.4%, boron nitride-silicon carbide composite powder is 0.3%, metal silicon powder is 1.7%, metal aluminum powder is 0.04%, organic fiber is 0.06%, and water reducer is 0.1%. Other conditions are the same, and the preparation method is as described in Example 1.

[0045] Comparative Example 1:

[0046] The comparative example provides a blast furnace branch ditch castable for ironmaking, wherein the mass percentages of the raw materials of the blast furnace branch ditch castable are: 11.8% of 15-8mm bauxite, 13.5% of 8-5mm bauxite, 12.5% ​​of 5-3mm bauxite, 11.5% of 3-1mm bauxite, 8.5% of 3-1mm plate-shaped corundum, 4.5% of 1-0mm plate-shaped corundum, 11% of 1-0mm silicon carbide, and 32.5% of 15-8mm bauxite. 5 mesh silicon carbide is 9.5%, alumina powder is 5%, silicon powder is 2%, high alumina cement is 1.8%, ρ-Al2O3 is 0.7%, andalusite is 1.3%, spherical asphalt is 2.25%, graphite powder is 1.8%, boron carbide is 0.3%, boron nitride-silicon carbide composite powder is 0.1%, metal silicon powder is 1.7%, metal aluminum powder is 0.02%, organic fiber is 0.05%, and water reducer is 0.18%. The preparation method of the castable is the same as that of the above embodiment.

[0047] Comparative Example 2:

[0048] The comparative example provides a blast furnace branch ditch castable for ironmaking, and the mass percentages of the raw materials of the blast furnace branch ditch castable are as follows: 11.6% of 15-8mm alumina, 13.8% of 8-5mm alumina, 11% of 5-3mm alumina, 11.8% of 3-1mm alumina, 8.9% of 3-1mm plate corundum, 4.4% of 1-0mm plate corundum, 12% of 1-0mm silicon carbide, 9.3% of 325 mesh silicon carbide, 4.8% of alumina micropowder, 2.4% of silicon micropowder, 2% of high alumina cement, 0.2% of ρ-Al2O3, 1% of andalusite, 2.3% of spherical asphalt, 1.6% of graphite powder, 0.25% of boron carbide, 0.35% of boron nitride-silicon carbide composite powder, 2% of metallic silicon powder, 0.03% of metallic aluminum powder, 0.07% of organic fiber, and 0.2% of water reducer. The preparation method of the castable is the same as that of the above embodiment.

[0049] Comparative Example 3:

[0050] The comparative example provides a blast furnace branch ditch castable for ironmaking, and the mass percentages of the raw materials of the blast furnace branch ditch castable are as follows: 11.7% of 15-8mm alumina, 14% of 8-5mm alumina, 12.8% of 5-3mm alumina, 12% of 3-1mm alumina, 8.7% of 3-1mm plate corundum, 4% of 1-0mm plate corundum, 10.5% of 1-0mm silicon carbide, 9% of 325 mesh silicon carbide, 5.3% of alumina micropowder, 2.5% of silicon micropowder, 1.6% of high alumina cement, 0.6% of ρ-Al2O3, 0.5% of andalusite, 2.33% of spherical asphalt, 2% of graphite powder, 0.2% of boron carbide, 0.4% of boron nitride-silicon carbide composite powder, 1.5% of metallic silicon powder, 0.02% of metallic aluminum powder, 0.05% of organic fiber, and 0.3% of water reducer. The preparation method of the castable is the same as that of the above embodiment.

[0051] Comparative Example 4:

[0052] The comparative example provides a blast furnace branch ditch castable for ironmaking, and the mass percentages of the raw materials of the blast furnace branch ditch castable are as follows: 12% of 15-8mm alumina, 13.8% of 8-5mm alumina, 12.7% of 5-3mm alumina, 12% of 3-1mm alumina, 9% of 3-1mm plate-shaped corundum, 4.8% of 1-0mm plate-shaped corundum, 10% of 1-0mm silicon carbide, 9.8% of 325 mesh silicon carbide, 4.5% of alumina micropowder, 1.5% of silicon micropowder, 1.7% of high alumina cement, 0.5% of ρ-Al2O3, 1.3% of garnet, 2.1% of spherical asphalt, 1.7% of graphite powder, 0.3% of boron carbide, 0.5% of boron nitride-silicon carbide composite powder, 1.6% of metallic silicon powder, 0.03% of metallic aluminum powder, 0.04% of organic fiber, and 0.13% of water reducer. The preparation method of the castable is the same as that of the above embodiment.

[0053] Among them, the content of boron nitride-silicon carbide composite powder in Comparative Example 1 is relatively low, the content of garnet in Comparative Example 3 is relatively low, and in Comparative Examples 1 to 3, the spherical asphalt particle size of 1-0.5mm accounts for 65%, and the particle size of 0.5-0.1mm accounts for 35%; in Comparative Example 4, the spherical asphalt particle size of 1-0.5mm accounts for 40%, and the particle size of 0.5-0.1mm accounts for 60%.

[0054] Performance Test:

[0055] The bulk density, flexural density and compressive strength of the branch ditch castables for ironmaking blast furnaces prepared in different proportions of the above-mentioned Examples 1-6 and Comparative Examples 1-4 were tested, and the range of the qualified product detection indexes is shown in Table 1 below:

[0056] Table 1 Qualified product testing index range

[0057]

[0058] The performance indicators of the iron ditch castables of the above-mentioned Examples 1-6 and Comparative Examples 1-4 are shown in Table 2:

[0059] Table 2 Performance indicators of Examples 1 to 6 and Comparative Examples 1 to 4

[0060]

[0061] It can be seen from the above table that the blast furnace branch ditch castables prepared by the ratio method of comparative examples 1-4, although their volume density, flexural strength and compressive strength can basically meet the standard range under low temperature conditions of 110°C, but when the temperature rises to 1450°C, their flexural strength and compressive strength are significantly weakened, and with the increase of time, the strength is significantly lower than the standard range, and does not meet the requirements.

[0062] The blast furnace branch ditch castables prepared by the proportioning methods of Examples 1-6 of the present invention have bulk density, flexural strength and compressive strength test results that are within the range of qualified product inspection indicators, whether under low temperature or high temperature adjustment. The castables prepared by the present invention have excellent refractory properties as well as high hardness and high strength, thereby significantly improving the performance and service life of the blast furnace branch ditch castables.

[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A blast furnace branch ditch castable, characterized in that: The mass percentage of each raw material component in the castable is: 15-8mm alumina is 11-12%, 8-5mm alumina is 13-14%, 5-3mm alumina is 11-13%, 3-1mm alumina is 11-12%, 3-1mm plate corundum is 8-9%, 1-0mm plate corundum is 4-5%, 1-0mm silicon carbide is 10-12%, 325 mesh silicon carbide is 9-10%, alumina powder is 4.5-5.5%, silicon oxide powder is 1.5-2.0%, 1.5-2.0% and 1.5-3.5% respectively. Micro powder is 1.5-2.5%, high alumina cement is 1.5-2%, ρ-Al2O3 is 0.5-1%, andalusite is 1-1.5%, spherical asphalt is 2-2.5%, graphite powder is 1.5-2%, boron carbide is 0.2-0.4%, boron nitride-silicon carbide composite powder is 0.3-0.5%, metal silicon powder is 1.5-2%, metal aluminum powder is 0.02-0.04%, organic fiber is 0.04-0.07%, and water reducer is 0.1-0.3%; The particle size of the boron nitride-silicon carbide composite powder is 800 mesh, of which boron nitride accounts for 22% and silicon carbide accounts for 78%; The surface of the graphite powder is modified by impregnation with trimethylaluminum, and the impregnation modification treatment method is: ① Add graphite powder into the reactor, add appropriate amount of n-hexane and toluene, and stir evenly; ② Add 5% trimethylaluminum by weight of graphite powder into the reactor and continue stirring evenly; ③ Heat the reactor, keep the temperature at 90-100°C, stir and react for 4-5 hours, so that trimethylaluminum reacts with the hydroxyl or carbonyl group on the surface of the graphite powder to form a chemical bond, and tightly bind the trimethylaluminum and graphite powder together; ④ After the reaction is completed, wash with a solvent to remove unreacted trimethylaluminum and other impurities; ⑤ Place the washed graphite powder in a ventilated drying room to dry it and remove the residual solvent to obtain trimethylaluminum-modified graphite powder; the ratio of the sites modified by trimethylaluminum to the total carbon edge sites is ≥60%.

2. The blast furnace branch ditch castable according to claim 1, characterized in that: The mass percentage of each raw material component in the blast furnace branch ditch castable is: 11.5% of 15-8mm bauxite, 13.5% of 8-5mm bauxite, 12.5% ​​of 5-3mm bauxite, 11.5% of 3-1mm bauxite, 8.5% of 3-1mm plate corundum, 4.5% of 1-0mm plate corundum, 11% of 1-0mm silicon carbide, 9.5% of 325 mesh silicon carbide, 5% of alumina powder, 2% of silicon powder, 1.8% of high alumina cement, 0.7% of ρ-Al2O3, 1.3% of garnet, 2.25% of spherical asphalt, 1.8% of graphite powder, 0.3% of boron carbide, 0.4% of boron nitride-silicon carbide composite powder, 1.7% of metallic silicon powder, 0.02% of metallic aluminum powder, 0.05% of organic fiber, and 0.18% of water reducer.

3. The branch ditch castable for an ironmaking blast furnace according to claim 1, characterized in that: Among the components of the castable, Al2O3 in bauxite is ≥87%, Fe2O3 is ≤1.5%; Al2O3 in plate-shaped corundum is ≥99%, Fe2O3 is ≤0.1%, SiO2 is ≤0.1%; SiC in silicon carbide is ≥97%, SiO2 is ≤0.4%, Fe2O3 is ≤0.3%, and free carbon is ≤0.5%; the particle size of alumina powder is ≤1μm; SiO2 in silicon powder is ≥95%; Al2O3 in high alumina cement is ≥80%; Al2O3 in ρ-Al2O3 is ≥92%; Al2O in andalusite is ≥90%; Al2O 3≥57%, particle size is 325 mesh; fixed carbon in spherical asphalt is ≥60%, ash content is ≤0.2%, volatile matter is ≤40%, particle size is 1-0.5mm accounts for 65%, particle size is 0.5-0.1mm accounts for 35%; fixed carbon in graphite powder is ≥94%, ash content is ≤1.6%, volatile matter is ≤1%; B4C in boron carbide is ≥95%, SiO2 is ≤0.1%, Fe2O3 is ≤0.25%; the particle size of metal silicon powder is 325 mesh; the particle size of metal aluminum powder is 200 mesh; the water reducer is a polyethylene glycol-based water reducer.

4. The blast furnace branch ditch castable according to claim 1, characterized in that: The branch ditch castable is used for the branch ditch of the iron tapping ditch of the blast furnace.

5. A method for preparing a branch ditch castable for an ironmaking blast furnace, using the branch ditch castable for an ironmaking blast furnace according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. According to the weight percentage, weigh 325 mesh silicon carbide, alumina powder, silicon powder, high alumina cement, ρ-Al2O3, andalusite, spherical asphalt, graphite powder, boron carbide, boron nitride-silicon carbide composite powder, metal silicon powder, metal aluminum powder, organic fiber, and water reducer respectively, add them into a mixer and stir for 5 to 7 minutes to obtain a small batch for standby use; S2, weighing 15-8mm alumina, 8-5mm alumina, 5-3mm alumina, 3-1mm alumina, 3-1mm plate-shaped corundum, 1-0mm plate-shaped corundum, and 1-0mm silicon carbide according to weight percentage, adding them into a mixer in sequence and stirring for 3 to 5 minutes to obtain compound granules; S3. While stirring the compound granular material, continuously and evenly add the compound small material to the mixer. The adding time of the compound small material is 3 to 5 minutes. After the addition is completed, the mixture of the compound granular material and the compound small material is evenly stirred for 3 to 5 minutes. After packaging, the blast furnace branch ditch castable can be obtained.

Citation Information

Patent Citations

  • Lightweight reformed main iron runner pouring material

    CN102101784A

  • Amorphous boron nitride-silicon carbide composite ceramic powder and preparation method thereof

    CN104446491A

  • High-temperature-resistant iron runner castable and preparation method thereof

    CN113620695A